The Association of GSTT1, GSTM1, and TNF-α Polymorphisms With the Risk and Outcome in Multiple Myeloma - Zmorzyński, Szymon; Popek-Marciniec, Sylwia; Szudy-Szczyrek, Aneta; Wojcierowska-Litwin, Magdalena; Korszeń-Pilecka, Iwona; Chocholska, Sylwia; Styk, Wojciech; Hus, Marek; Filip, Agata A. (Frontiers in Oncology, 2019)
Oxidative stress and systemic inflammation are closely linked with increased risk of cancer development. Tumor necrosis factor alpha (TNF-α) is one of the pro-inflammatory cytokines. Glutathione S-transferases (GSTs) are enzymes involved in oxidative stress handling. Polymorphisms of genes encoding mentioned molecules may potentially influence the risk and the outcome in neoplastic diseases. Multiple myeloma (MM) is a haematological malignancy characterized by clonal, atypical plasma cell proliferation. In the present study we investigated the association of deletion polymorphisms in GSTT1/GSTM1 genes and single nucleotide polymorphisms (SNPs) in the TNF-α gene at positions -308/-238 with the risk and outcome in MM and sensitivity to bortezomib under in vitro conditions. One hundred newly diagnosed MM patients and 100 healthy blood donors were genotyped by means of multiplex PCR (for GSTs) and PCR-RFLP (for TNF-α). In a subgroup of 50 MM patients, bone marrow cells were treated with bortezomib in vitro. Patients with -238GA+AA or GSTT1-null genotypes had 2.0 (p=0.002) or 2.29 (p=0.013) fold increased risk of MM. The interaction effects and risk of MM were observed in GSTT1/GSTM1-null (OR=2.82, p=0.018), -308/-238GA+AA (OR=5.63, p<0.001), as well as in all combinations of -308 with GSTs. The -308/-238GA+AA genotypes in comparison to GG were associated with earlier MM onset – 61.14 vs. 66.86 years (p=0.009) and 61.72 vs. 66.52 years (p=0.035), respectively. Patients with GSTM1-present had shorter progression-free-survival (15.17 vs. 26.81 months, p=0.003) and overall-survival (22.79 vs. 34.81 months, p=0.039) compared with GSTM1-null. We did not observe relationship between response rate and studied polymorphisms. The in vitro study revealed significantly higher number of apoptotic cells at 12nM of bortezomib in GSTT1-present, GSTM1-null/present, -308GG and -238GG/GA+AA genotypes. Our findings comprise large analysis of studied polymorphisms in MM.